2020
DOI: 10.1007/s11356-020-08656-w
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposure of pyriproxyfen to pregnant female mice causes developmental abnormalities in prenatal pups

Abstract: The continuous exposure to conventional pesticides leads to severe health and environmental issues especially at prenatal stage during developmental period. Herein, we aimed to investigate the anomalies due to repeated exposure of pyriproxyfen in pregnant female mice and their neonates. Twenty-four pregnant female mice were repeatedly administered with pyriproxyfen at 30, 100, 300, and 1000 mg/kg by oral gauge from gestation day (GD) 7 to gestation day 17 and six females were given distilled water in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…This study found that lufenuron reduced male body weight in rats compared to the control group. It is in conformity with Basal et al (2020) observation of a reduction in the body mass of female rats subjected to lufenuron and Shahid and Saher (2020) observation that a pregnant mouse was exposed to pyriproxyfen had significantly less body weight gain.…”
Section: Discussionsupporting
confidence: 91%
“…This study found that lufenuron reduced male body weight in rats compared to the control group. It is in conformity with Basal et al (2020) observation of a reduction in the body mass of female rats subjected to lufenuron and Shahid and Saher (2020) observation that a pregnant mouse was exposed to pyriproxyfen had significantly less body weight gain.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with other published data where body weight was found to impair when mice were prenatally treated with pesticide (Guo et al, 2018; Syed et al, 2016) and slow physical growth of litter was observed when female pregnant rats were repeatedly exposed to pyriproxyfen (Shahid & Saher, 2020). A study has also shown that the administration of rotenone in the dams reported that treatment of rotenone in the dams reduced the body weight of the fetus and placental weight (Krishna & Muralidhara, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Exposure to 1.66 µg mL −1 PYR for 96 h caused significant alterations in zebrafish heart anatomy, including heart muscle thinning, hyperemia, and pericardial edema [ 40 ]. The influence of PYR at the histological level was also demonstrated in female mice after the administration of 30, 100, 300, and 1000 mg kg −1 which led to an increase in the number of glial cells, vacuolization, and degenerated neurons [ 41 ].…”
Section: Introductionmentioning
confidence: 99%